Development of conjugated secondary antibodies for wildlife disease surveillance - Ochai, Sunday O.; Crafford, Jan E.; Kamath, Pauline L.; Turner, Wendy C.; van Heerden, Henriette (Frontiers in Immunology, 2023)
Disease monitoring in free-ranging wildlife is a challenge and often relies on passive surveillance. Alternatively, proactive surveillance that relies on the detection of specific antibodies could give more reliable and timely insight into disease presence and prevalence in a population, especially if the evidence of disease occurs below detection thresholds for passive surveillance. Primary binding assays, like the indirect ELISA for antibody detection in wildlife are hampered by a lack of species-specific conjugates. In this study, we developed anti-kudu (Tragelaphus strepsiceros) and anti-impala (Aepyceros melampus)immunoglobulinspecific conjugates in chickens and compared them to the binding of commercially available protein-G and protein-AG conjugates, using an ELISA-based avidity index. The conjugates were evaluated for cross-reaction with sera from other wild herbivores to assess future use in ELISAs.The developed conjugates had a high relative avidity of > 70% against kudu and impala sera. The commercial conjugates (protein-G and protein-AG) had significantly low relative avidity (< 20%) against these species. Eighteen other wildlife species demonstrated cross-reactivity with a mean relative avidity of > 50% with the impala and kudu conjugates and < 40% with the commercial conjugates.These results demonstrate that species-specific conjugates are important tools for the development and validation of immunoassays in wildlife, and for the surveillance of zoonotic agents along the livestockwildlife-human interface.With the current increase in emerging and re-emerging disease outbreaks of both veterinary and human importance, there has been an urgent need for evidence-based methods for measuring both infection incidence Deleted: .